The effect of blood glucose level in experimental of sepsis rats on mortality - Yaşar, Mehmet Akif; Ödeş, Ramazan; Kizirgil, Ahmet; Üstündağ, Bilal; Yaşar, Demet; Bulut, Yasemin; Demirel, İsmail (Fırat University, 2007)
Objectives: The recent multitask studies made in the intensive care unites, it is detected that blood glucose level is one of the most determining factors for mortality. In this study the blood glucose level in experimental of sepsis in rats is altered and the effect of blood glucose level alterations on mortality is studied. Material and Methods: 60 wistard rats are included into the study. An artificial sepsis model is designed in all subjects by matching an intraperitoneal injection of 5 mg/kg E.Coli LPS in order to determine the bacterial translocation. The subjects are divided into two groups which include the group coith blood glucose level between 85-110 and the diabetic group with blood glucose level between 180-215. Tissue samples (mesenteric lymph node, liver, spleen) are taken from the subjects which died after shocoing symptoms of shock. Bacterial translocation is studied by using PCR and blood culture methods. Results: All the subjects in the diabetic group died in the first five day and all the subjects in the control group died in the first twelve days after LPS application. The mortality rate in the diabetic group is detected as statistically significant higher than the mortality rate in the control group (p

Giriş: Son yıllarda yoğun bakım ünitelerinde yapılan çok merkezli çalışmalarda mortalitenin önemli belirleyicilerinden birisinin de kan glukoz düzeyi olduğu saptanmıştır. Bu çalışmada sepsis oluşturulan ratlarda sadece kan glukoz düzeyi değişken tutulup bunun mortaliteye etkileri araştırıldı. Gereç ve Yöntem: 60 adet wistard türü rat çalışmaya alındı.Tüm hayvanlarda bakteriyel translokasyonu tespit edebilmek amacıyla; E. Coli lipopolisakkarit'i (LPS) 5 mg/kg intraperitoneal olarak uygulanarak sepsis modeli oluşturuldu. Denekler kontrol grubunda kan glukoz düzeyi 85-110 mg/dl olanlar ve diabetik grupta ise 180-215 mg/dl arasında olanlar olmak üzere iki gruba ayrıldı. Şok belirtileri saptandıktan sonra ölen ratlardan, doku örnekleri (Mezenter lenf nodu, karaciğer, dalak) alındı. Polymerase Chain Reaction (PCR) ve kültür yöntemi ile bakteriyel translokasyon Araştırıldı. Bulgular: Diyabetik gruptaki ratlara LPS uyguladıktan sonra 5 gün içinde tamamı, kontrol grubunda ise 12 gün içinde tamamı kaybedildi. Mortalite hızı diabetik grupta, kontrol grubuna göre yüksek olarak bulundu (p
Sepsis Oluşturulan Ratlarda Kan Glukoz Düzeyinin Mortaliteye Etkisi